Hustle bustle bugs - Bailey, Catherine (Children's story writer); Eldridge, Lauren (New York : Little, Brown and Company, 2022)
"Bugs, including ants, beetles, grasshoppers, and more, have unique skills that combine to create a safe and welcoming world for everyone-even people!-to live in"--
Ages 4-8.
Keywords: Insects -- Juvenile literature; Insects -- Behavior -- Juvenile literature